Home range and resource selection by animals constrained by linear habitat features: an example of Blakiston's fish owl. Issue 6 (19th August 2013) - Slaght, Jonathan C.; Horne, Jon S.; Surmach, Sergei G.; Gutiérrez, R.J.; Stephens, Phil
Summary Typically in resource selection studies, the spatial extent of a home range is defined first and then the available resources within that perimeter are estimated. However, the home ranges (or habitats) of some animals are constrained by linear environmental features (e.g. rivers, shorelines). Traditional home range estimators often overestimate home range extent for such species, which can lead to spurious estimation of resource availability and selection. We used a synoptic model of space use to explicitly account for resource selection of a species constrained by linear features in its environment to compare with traditional home range estimators. We used the endangered Blakiston's fish owl Bubo blakistoni in the Russian Far East as our example. Mean annual home range size (± standard error) was more than three times larger when using kernel methods (30·3 ± 15·1 km2) than when using the synoptic model (9·4 ± 2·0 km2, n = 7). Fish owls showed strong selection for areas within valleys, closer to waterways, closer to patches of permanently open water and with greater channel complexity than available sites. Synthesis and applications. The synoptic model solves a long‐standing problem in home range and resource selection studies because it provides an objective way to estimate the space use of a species whose habitat is constrained by linear features in its environment. Improvements in the accuracy of such estimations can lead to identification of important resources across landscapes, the development of more rigorous site‐specific or landscape‐scale management plans, and to scientifically defensible conservation or threat mitigation measures.